Automated Farm Machinery Rental Platform (in Pallisa (District) - Derick Mwigo (Uganda Christian University, 2025)
Agricultural productivity in Pallisa District continues to face challenges due to limited access to modern farm machinery, high costs of ownership, and inefficient manual rental processes. This project proposes the development of an Automated Farm Machinery Rental Platform designed to streamline the acquisition and utilization of agricultural equipment. The platform will provide farmers with affordable, timely, and transparent access to machinery such as tractors, planters, and harvesters through a digital interface that supports booking, scheduling, and payment automation. By integrating technology into the rental system, the project aims to reduce labor intensity, improve efficiency, and promote equitable distribution of resources across the district. The platform will also enhance accountability by maintaining digital records of transactions and usage, thereby minimizing misuse and ensuring sustainability. Ultimately, this initiative seeks to empower farmers, strengthen food security, and contribute to socio-economic development in Pallisa District through organized, accessible, and innovative service delivery.
Postgraduate Research